The Importance of Understanding Exponent Number Concept in Science Scope: Students' Abstraction Thinking Level in Problem Solving - Siti Faizah; Slamet Arifin; Intan Sari Rufiana; Sri Rahayuningsih; Mohammad Yusuf Randy; Nurzatulshima Kamaruddin; Imam Rofiki; Ali Shodikin (Jurnal Penelitian Pendidikan IPA, 2024)
Mathematics is closely related to science because both require the ability to analyze, think logically, and systematically to understand. This study explores students' level of abstraction thinking in understanding the concept of exponent numbers and its implementation in science. This research uses a qualitative approach. The subjects in this study were students of the master's program in basic education. The data collection techniques used were tests and interviews. The results showed differences in identifying exponent numbers in low and high abstraction level students. Low abstraction level students perform problem-solving stages, such as identifying and writing down every information listed in the problem, using mathematical symbolization, performing number operations according to problem understanding, and checking again. Meanwhile, high abstraction level students performed problem-solving stages, such as identifying every piece of information in the problem without writing it on the worksheet, not writing the results of their understanding explicitly on the worksheet, not writing explicitly the model to be used, performing number operations without paying attention to the type of number because they already understood and they made a conclusion. Both level students applied the concept of exponent numbers in science for writing units and density.